HUBUNGAN ANTARA SELF-COMPASSION DENGAN RESILIENSI PADA PENDERITA SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) DI KOMUNITAS LUPUS PANGGON KUPU SEMARANG - Hilda Amanda; Siswati Siswati (Jurnal EMPATI, 2019)
This study aims to determine the relationship between self-compassion and resilience. Patients with Systemic Lupus Erythematosus (SLE) that can be compassionate toward themselves will be able to increase resilience they have in order to face stressful condition caused by the disease. The subject in this study was patients with SLE from Community of Lupus, Panggon Kupu Semarang. The sample was obtained using convenience sampling technique, resulted with 38 subjects. The data was earned using two different Likert’s scale model, those were Self-compassion’s Scale (contains 31 valid items, α = 0,925) and Resilience’s Scale (contains 47 items, α = 0,927) which has been tested before on 30 patients with SLE. The data was analysed using simple regression analysis. The result of this research showed that there was a significant and positive relationship between self-compassion and resilience with rxy = 0,617 and p = 0,000 (p < 0,05). Self-compassion effectively contributes 38,1% to resilience in patients with Systemic Lupus Erythematosus (SLE) and 61,9% is contributed by other factors that were not measured in this study.